Implementasi Forward Chaining Method Pada Sistem Pakar Untuk Deteksi Dini Penyakit Ikan - Linda Perdana Wanti; Syahrur Romadhon (Infotekmesin, 2020)
This study aims to create a computer based intelligent system to detect freshwater fish disease.  Problems often faced by fish farmers, especially freshwater fish, are fish diseases that begin with signs such us wounds on the surface of the fish’s body, bleeding on the gills, fish’s stomach which suddenly enlarges and is filled with fluid, the release of fins or the tail of the fish which results in the death of cultivated fish, thereby reducing freshwater fish production. The expert system developed to implement the forward chaining method which starts with tracking the symptoms experienced by fish to determine the preventive action that must be taken by bringing the symptoms to the system. System development in this study uses extreme programming (XP) where the flexibility of this method supports all changes that occur when developing an expert system to detect fish diseases. The output of the research carried out in the form of an expert system that provides information about freshwater fish diseases, the cause and how to overcome them.